Dissection of Bmi1-mediated epigenetic regulation of target genes in glioblastoma. (31st January 2018) - Ricci, Barbara; Guglielmi, Loredana; Barnes, Michael; Marino, Silvia
Abstract: Glioblastoma multiforme (GBM) is the most malignant adult brain tumour. Recent studies on gliomagenesis have provided new insights into the genomic and epigenomic landscape of this disease. Particular interest has been focused on the Polycomb group proteins (PcG), which are chromatin modifiers regulating heritable gene repression. Our previous data has shown that overexpression of the PcG gene Bmi1 in mouse embryonic neural stem cells (NSCBmi1Over) increases self-renewal and proliferation without inducing neoplastic transformation.However, repression of Bmi1 in patient-derived GBM initiating cells (GBM-IC) and in a mouse model of GBM, impairs both self-renewal and proliferation, demonstrating that Bmi1 plays a crucial role in tumour maintenance. In genome wide transcriptomic and histone modification analysis we identified 180 genes specifically deregulated in mouse GBM-IC overexpressing Bmi1 as compared to mouse NSC. Ingenuity Pathway Analysis (IPA) revealed a significant enrichment in canonical pathways such as axonal guidance and Eph/ephrin signalling with a similar signature found in publicly available human GBM-IC ChIPSeq data. Functional assays in vitro demonstrated that EfnA5 is a direct target of Bmi1 that mediates Bmi1 impact on cell morphology, proliferation and migration in murine GBM-IC. Taken together, these data suggest EfnA5 as a potential druggable target in GBM overexpressing Bmi1.